CHARACTERISTICS AND COMPETENCIES OF DPRD MEMBERS TO SUPPORT GOOD GOVERNANCE IN THE REGION - Idris, Kholik; Rattanapun, Supot (Penerbit Lafadz Jaya, 2024)
This paper aims to examine the characteristics and competencies of members of the Regional Representatives Council (DPRD) in supporting good governance in the region. This research uses a normative juridical method with a document study approach as a data collection technique. The main focus of the research is on the characteristics, competencies, and behavioural patterns of DPRD members required to support the principles of good governance, such as transparency, accountability, and community participation. The results show that the ideal DPRD member must have high integrity, good communication skills, and a deep understanding of public policy. In addition, open and inclusive communication patterns and the use of information technology are essential to increase public participation in the legislative process. The findings are expected to provide recommendations for improving the quality of DPRD members in carrying out their functions and encouraging active community participation in public decision-making.